8.12 EVALUATION OF THE EFFECTIVENESS OF THE USE OF INNOVATIVE TRACK EQUIPMENT IN THE REPAIR AND MAINTENANCE OF RAILWAY TRACKS - Mirkhanova Mavjuda Mikhailovna senior Lecturer TSTU, Eshonov Farkhod Fayullakhodjayevich senior Lecturer TSTU, Khamidov Maqsud Khamidov Maqsudzhan Kamolovich assistant TSTU (Innovative technologies in construction Scientific Journal, 2024)
The article considers the issues of using innovative technology for the current maintenance and repair of a railway track. The KGT-4RS multifunctional machine was chosen as a modern track equipment. The versatility of this vehicle lies in the fact that it is capable of operating on a combined course (in particular, on railway and automobile), as well as performing various types of repair work by changing a large range of attachments. The paper presents the results of a comparative assessment of the use of KGT-4RS, the VPR-02 track machine and manual labor to perform the operation of tamping sleepers when straightening the path. It is noted that manual labor it allows the replacement of sleepers without closing the crossings, but is inefficient, while specialized machines perform a large amount of work, but it requires the closure of the crossings. To confirm the economic feasibility of using a new generation of technology KGT-4RS has developed a methodology for evaluating the economic efficiency of the use of innovative technology when performing various types of work on the current maintenance and repair of the track. As the main one The criterion for calculations is the value of the cost of a unit of travel work. According to the calculation results , it was found that the lining of sleepers in the amount of up to 10 pieces is economically advantageous to carry out manually, from 10 up to 38 sleepers are equipped with the KGT-4RS multifunctional machine, and over 38 sleepers are equipped with the VPR-02 track machine. The proposed methodology takes into account the current operational, annual and one-time costs of operation-It allows you to choose a cost-effective machine to perform certain tasks on the maintenance of the railway track. Keywords: track equipment, KGT-4RS machine, economic efficiency, repair, railway track. In modern conditions, in order to increase the efficiency of the transport complex, the issue of creating a conditions that ensure the innovative development of high-tech machines and new technologies, which fully meets the main tasks defined by the Strategy for the Development of Railway Transport in the Russian Federation until 2030 [1]. The priority areas of innovative development of the transport complex and, in particular, the food industry of JSC "Russian Railways" include the introduction of innovative repair and maintenance technologies -for the maintenance of the railway track on road networks in order to achieve high efficiency of results with high quality of work and transportation safety.